An Overview on NO-Rich Diet for Lifestyle-Related Diseases - Jun Kobayashi; Kazuo Ohtake; Hiroyuki Uchida (Highlights on Medicine and Medical Research Vol. 1, 2021)
Decreased nitric oxide (NO) availability due to obesity and endothelial dysfunction might be causally related to the development of lifestyle-related diseases such as insulin resistance, ischemic heart disease, and hypertension. In such situations, instead of impaired NO synthase (NOS)-dependent NO generation, the entero-salivary nitrate-nitrite-NO pathway might serve as a backup system for NO generation by transmitting NO activities in the various molecular forms including NO and protein S-nitrosothiols. Recently accumulated evidence has demonstrated that dietary intake of fruits and vegetables rich in nitrate/nitrite is an inexpensive and easily-practicable way to prevent insulin resistance and vascular endothelial dysfunction by increasing the NO availability; a NO-rich diet may also prevent other lifestyle-related diseases, including osteoporosis, chronic obstructive pulmonary disease (COPD), and cancer. This review provides an overview of our current knowledge of NO generation through the entero-salivary pathway and discusses its safety and preventive effects on lifestyle-related diseases. Although the role of diet-derived NO activity in lifestyle-related diseases is complex and remains to be fully elucidated, the intake of nitrate as a nutrient in vegetables might be beneficial to human health as a result of synergistic effects with other nutrients present in vegetables, and would be recommended as a nutritional approach to the prevention and treatment of the lifestyle related diseases.